FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKSUAL BERISIKO PADA REMAJA - Kusumawardani, Emi; Herniyatun, Herniyatun; Amin, Hadriyani; Pangaribuan, Resmi; Perestroika, Grhasta Dian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Sexual behavior is any behavior driven by sexual desire, either with the opposite sex or with the same sex. Initial data survey conducted at SMA N 12 Pekanbaru from 15 respondents, 15 of them claimed to have dated, and 10 of them were currently dating, 9 respondents considered that dating was a natural thing, 8 respondents claimed to be dating under the age of 15, 7 respondents were known by their parents to have a boyfriend, even their boyfriend had visited their house and vice versa they had also visited their boyfriend's house, 6 respondents claimed to have embraced their boyfriend, and they considered it a natural thing to do. The purpose of the study was to determine the Factors Associated with Sexual Behavior in Class XI Adolescents at SMAN 12 Pekanbaru in 2022. The type of research is quantitative using a cross sectional design on a sample of 108. The sampling technique used proportionate stratified random sampling. The results of the study were there was a relationship between knowledge (p value 0.026; POR 2.6), peers (p value 0.005; POR 4.3) and family harmony (p value 0.032; POR 2.5) with sexual behavior in adolescents. It is suggested that there is a need for programs that can increase knowledge such as counseling, disseminating correct sexual information and increasing parental supervision efforts for teenagers.Keywords: Family Harmony, Knowledge, Adolescents, Peers